The Assessment Instrument for Mapping Potential Vocational Skills for Special Need Children and VET Handbook for Disabilities - Sylvia, Aurellia Agatha (GRAB KIDS: Journal of Special Education Need, 2025)
Vocational education for people with disabilities in Indonesia faces significant challenges, despite their lower unemployment rate compared to non-disabled people. This may be due to a lack of understanding of their potential. Vocational education plays an important role in preparing children with disabilities to compete in the world of work, with support from parents and the community. Previous research shows that the implementation of vocational skills programs is often not on schedule and there is a lack of adequate evaluation instruments. This study aims to design an assessment instrument and a Vocational Education and Training (VET) guidebook to improve the effectiveness of vocational education for people with disabilities, so that they can achieve independence and contribute productively to society. Library research was used in this study to understand the needs and challenges faced by children with disabilities and to develop recommendations based on data from journals or previous research. The results showed that the instrument designed was able to effectively identify vocational potential, while the Vocational Education and Training (VET) guidebook provided practical guidance for educators and people with disabilities to improve vocational skills. Keywords: Assessment Instrument, Potential Vocational skills, Vocational Education and Training VET, Economic Welfare Improvement, Disability.